Marine Ecotourism Potential Of Sironjong Gadang Island Pesisir Selatan Regency Of West Sumatra Province - Bayu Putra U Irawan; Aras Mulyadi; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in December 2013 in coastal area of Sironjong Gadang Island of Pesisir Selatan Regency of West Sumatra Province. The aim was to determine its potential and suitability level of Sironjong Gadang Island to serve as marine ecotourism area. The method used in this study was a survey method and observation stations determination was done by purpossive sampling. Based on the research results, Sironjong Gadang Island was potential to be developed as marine tourism area. According to the category, tourist boating, banana boat and jet ski were included into the category of highly suitable (S1) at each station, recreation and swimming at every station were included as quite fit category (S2), and for the snorkling and diving at station II and III were included into the appropriate category (S2), whereas at the station I was included into the category of corresponding conditional (S3).Key Words: Level of Compliance, Marine Ecotourism, Sironjong Gadang Island